The Kabbalistic Scholars of the Antwerp Polyglot Bible - Wilkinson, R.J (Studies in the History of Christian Traditions, 2007)
This work exposes the eschatological timetable which propted the petition for the Antwerp Polyglot and the Christian kabbalistic motivation of the scholars who worked on the text. This tradition is then traced to the 1584 Paris edition of the Syriac New Testament.